Evaluation of the effect of clinical validation of out of hours critical laboratory results. (March 2016) - Chandrajay, Deepak; Narayanan, Deepa; Barth, Julian H
Aim: The aim of the study was to review the clinical validation process of out of hours critical biochemistry results by a clinical biochemist and its effect on primary care services. Methods: A prospective study was conducted of all critical results for primary care patients who were analysed out of hours. The nine-month study period was conducted between June 2013 and February 2014. The data collected include patients' age, clinical details, critical results and the urgency of result communicated. The patients' subsequent attendance rate at the emergency department in the local hospital was reviewed. Results: A total of 311 out of hours critical results were identified in the laboratory. After clinical validation, 110 (35.4%) results were telephoned urgently and 155 (49.8%) results were deferred to the next day. Forty-six (14.8%) results were not telephoned. Following the urgent result communication, 53/110 (48.2%) patients attended the hospital emergency department within 24 h and 17/110 (15.5%) had their repeat blood test by their general practitioner surgery within 48 h. When the result was telephoned during working hours the next day, only 15/155 (9.7%) attended the hospital acute services within 48 h and 16/155 (10.3%) had repeat blood test at their general practitioner surgery. Conclusion: In our practice, the clinical validation of out of hours critical results by a clinical biochemist is associated with a reduction in the number of results telephoned when compared against the critical limits list recommended by the Royal College of Pathologists and may focus out of hours clinical activity on more suitable patients.